Self-driven current generation in turbulent fusion plasmas. (25th June 2019) - Wang, W.X.; Hahm, T.S.; Startsev, E.A.; Ethier, S.; Chen, J.; Yoo, M.G.; Ma, C.H.
Abstract: Global gyrokinetic simulations with self-consistent coupling of neoclassical and turbulent dynamics show that turbulence can significantly affect plasma self-driven mean current generation in tokamaks. The current amplitude, profile and associated phase space structures can all be modified. Turbulence can significantly reduce the current generation in the collisionless regime, generate current profile corrugation near the rational magnetic surface and nonlocally drive current in the linearly stable region—all these are expected to have a radical impact on broad tokamak physics. Both electron parallel acceleration and residual stress from turbulence play crucial roles in turbulence-induced current generation.